Rancang Bangun Aplikasi Manajemen Gudang Pada Percetakan Dolphin Corp - Muhammad Ikhsan; Helmina Helmina; Rian Dani (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2023)
Technology has a very important role in creating quality human resources. In this case, technology also does not escape incoming and outgoing goods transactions, as happened with Dolphin Corp. Dolphin Corp is one of the printing companies in Jambi City which serves various types of printing, both small and large scale. The services provided by Dolphin Corp, such as printing invitations, books, calendars, food packaging, brochures, magazines and so on, are all carried out based on requests from consumers after the consumer makes payment. The system used to store data on incoming goods still uses physical records in books, where there is no system that functions optimally to increase the amount of stock, reduce the amount of stock and record stock reports.